2005
DOI: 10.1345/aph.1e381
|View full text |Cite|
|
Sign up to set email alerts
|

Search for Predictors of Nontherapeutic INR Results with Warfarin Therapy

Abstract: In the absence of readily identifiable predictors, only higher warfarin dosing and/or more frequent monitoring (possibly with point-of-care/home monitoring devices) may minimize the time that INRs are subtherapeutic, especially in patients receiving low-dose and/or high-intensity anticoagulation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Drug interactions can influence warfarin dose and risk of hemorrhage 7 , 42 . The increase in risk can result from concomitant use of drugs such as non‐steroidal anti‐inflammatory drugs or antiplatelet agents, 43 or drugs that alter warfarin pharmacokinetics, including CYP2C9 inhibitors ( e.g ., amiodarone), CYP2C9 inducers ( e.g ., rifampin), or CYP2C9 substrates ( e.g ., losartan) 44 , 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Drug interactions can influence warfarin dose and risk of hemorrhage 7 , 42 . The increase in risk can result from concomitant use of drugs such as non‐steroidal anti‐inflammatory drugs or antiplatelet agents, 43 or drugs that alter warfarin pharmacokinetics, including CYP2C9 inhibitors ( e.g ., amiodarone), CYP2C9 inducers ( e.g ., rifampin), or CYP2C9 substrates ( e.g ., losartan) 44 , 45 .…”
Section: Methodsmentioning
confidence: 99%
“…There were two cross-sectional studies that reported on the effect of smoking on INR. [26] , [27] However, we were unable to pool and analyze the data of these studies because one expressed INR as continuous data, and the other expressed it as categorical data.…”
Section: Effect Of Smoking On Inrmentioning
confidence: 99%
“…Information on self-reported race, indication for therapy, demographics, height and weight, concomitant medications and co-morbid conditions is documented. Lifestyle and socioeconomic data included smoking, alcohol use (number of alcoholic drinks per week) [19][20][21], education, annual household income, medical insurance, compliance, level of physical activity [22,23], and dietary vitamin K intake (number of servings of foods rich in vitamin K per week). [24] All patients are followed for up to two years from initiation of therapy at monthly intervals.…”
Section: Data Collectionmentioning
confidence: 99%